2008
DOI: 10.1016/j.cub.2008.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Systems for Understanding Action Intentions

Abstract: How humans understand the intention of others' actions remains controversial. Some authors have suggested that intentions are recognized by means of a motor simulation of the observed action with the mirror-neuron system [1-3]. Others emphasize that intention recognition is an inferential process, often called "mentalizing" or employing a "theory of mind," which activates areas well outside the motor system [4-6]. Here, we assessed the contribution of brain regions involved in motor simulation and mentalizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
217
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 307 publications
(263 citation statements)
references
References 27 publications
28
217
3
Order By: Relevance
“…Unlike previous work that typically demonstrated an action-goal (to grasp an ear) was prioritized (hierarchal goal representation) at the expense of biological kinematics Hamilton, Brindley, & Frith, 2007;Hayes, Hodges, Scott, Horn, & Williams, 2007;Wohlschlager, Gattis, & Bekkering, 2003), we showed the attainment of an end-state-target 13 goal did not affect the representation of biological kinematics. Our findings build upon the aforementioned effects by indicating top-down and lower-level processes operate within an embedded system that is less hierarchal, and perhaps more complementary (Buxbaum & Kalénine, 2010;de Lange, Spronk, Willems, Toni, & Bekkering, 2008;Heyes, 2011), with the contribution of these processes modulated by the nature of task context. When the biological movement kinematics are novel, as per our atypical biological motion, both processes operate to represent movement kinematics and the end-state-target goal.…”
Section: Discussionsupporting
confidence: 68%
“…Unlike previous work that typically demonstrated an action-goal (to grasp an ear) was prioritized (hierarchal goal representation) at the expense of biological kinematics Hamilton, Brindley, & Frith, 2007;Hayes, Hodges, Scott, Horn, & Williams, 2007;Wohlschlager, Gattis, & Bekkering, 2003), we showed the attainment of an end-state-target 13 goal did not affect the representation of biological kinematics. Our findings build upon the aforementioned effects by indicating top-down and lower-level processes operate within an embedded system that is less hierarchal, and perhaps more complementary (Buxbaum & Kalénine, 2010;de Lange, Spronk, Willems, Toni, & Bekkering, 2008;Heyes, 2011), with the contribution of these processes modulated by the nature of task context. When the biological movement kinematics are novel, as per our atypical biological motion, both processes operate to represent movement kinematics and the end-state-target goal.…”
Section: Discussionsupporting
confidence: 68%
“…Recent findings indicate that the action observation system is sensitive to the context an action occurs in and may code the meaning or goal of the action rather than the exact way in which the action is performed (Rijntjes et al, 1999;Bekkering et al, 2000;Gergely et al, 2002;Gazzola et al, 2007;Jonas et al, 2007;Newman-Norlund et al, 2007;de Lange et al, 2008). We postulate that in the observation of actions to which it is not easy to ascribe a clear meaning or goal (as in the present study), the cortical motor system does simulate the specific basic motor properties of the observed action.…”
Section: Discussionsupporting
confidence: 50%
“…They showed that, although the parieto-frontal mirror mechanism is active in all conditions in which the motor task has to be directly understood, when volunteers were required to judge the reasons behind the observed actions, there was an activation of a sector of the anterior cingulate cortex and of other areas of the so-called 'mentalizing network' 92 . Activation of the same network was also shown in a study that investigated unusual actions performed in implausible versus plausible contexts 93 , as well as in a study on the neural basis of reason inference in non-stereotypical actions 94 .…”
Section: Motor Actionmentioning
confidence: 99%